Production of furfural with high yields from corncob under extremely low water/solid ratios - Qiong Wang (2018)
© 2018 Elsevier Ltd Furfural is considered to be one of the top 30 potential chemicals derived from lignocellulosic biomass. Compared to conventional diluted acid catalysis, furfural production from lignocellulose was significantly improved by the addition of an immiscible organic solvent into the diluted acid solution. However, high conversion is usually achieved under a high water/solid ratio (>1, v/m), and the furfural product is distributed in both the organic solvent phase and the aqueous phase, leading to difficulty of furfural recovery and increasing the cost of furfural production. The present work investigated corncob conversion in a diluted sulfuric acid-toluene biphasic system with extremely low water/solid ratios (≤1). It was found that a high furfural yield (65.67 mol%) was achieved in a very short time (10 min) under a high solid loading of 200% (in the aqueous phase) under the conditions of 1.5 MPa N2, 0.5:1 water/solid ratio (v/w), 10:1 toluene/solid ratio (v/m), and 3.85 wt% H2SO4(in the aqueous phase). After the reaction, no aqueous phase existed, and furfural was completely accumulated in the toluene phase. Further research showed that the majority of the furfural content (84.73%, GC-MS detection) was in the toluene phase, which is beneficial for its recovery. This work provides an effective and inexpensive method for the production of furfural from lignocellulose.